Social-ecological resilience: Knowledge of agrobiodiversity by campesinos and migrants in the face of global changes - Ibarra, Jose Tomas; Caviedes, Julian; Monterrubio-Solis, Constanza; Barreau, Antonia; Marchant, Carla (My University, 2024)
There is concern that agrobiodiversity is being irreversibly eroded in the face of agricultural industrialization. While academic and policy debates stress loss of landraces, little attention has been paid to evaluating how agricultural knowledge systems endure in response to broader social-ecological changes (i.e., "system's resilience"). For being resilient, agricultural knowledge systems should incorporate new information (modern seed varieties) whilst maintaining its traditional components (landraces) and functions. However, the loss or continuing utilization of landraces may be influenced by several social-ecological filters, which are processes that selectively remove varieties according to their phenotype, local uses, or value. We examined the resilience of agricultural knowledge systems in the southern Andes. These systems include the knowledge of landraces and modern varieties by campesinos and lifestyle migrants. We further assessed the association of social-ecological filters with the knowledge of agrobiodiversity. Over four years (2018-2022), we used mixed-methods including semi-structured interviews with gardener experts and conducted knowledge exercises of seed varieties and surveys of gardeners (n = 132). We assessed the association of 'knowledge score on varieties' (general, landraces, and modern) with a priori-defined social-ecological filters. Gardeners with more proficient knowledge of landraces were more knowledgeable of modern varieties too. The general knowledge of agrobiodiversity and the knowledge of landraces, but not of modern varieties, was higher for campesinos than migrants. The main seed source of gardeners, the participation in seed exchanges, gardeners' origin, and gardeners' age were the social-ecological filters that influenced gardeners ' knowledge of agrobiodiversity. We highlight that socialecological, small-scale farming systems, are being resilient when they have the capacity of incorporating new information (knowledge of modern varieties) whilst maintaining their identity (knowledge of landraces) without undergoing a major shift in their basic structures and functions in this Important Agricultural Heritage Site and Global Biodiversity Hotspot, and beyond.
Keywords: agriculture; seeds; social-ecological filters; important agricultural heritage systems; small-scale farmers; chile